Application of Game Based Learning Model to Improve Volleyball Learning Outcomes for Students at State Islamic High School - Pinkan Dhita, Pinkan Setya Dhita; Wahyudi, Agung (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
This study aims to analyze the influence of the Game-Based Learning model on improving volleyball learning outcomes of students in class X MAN 2 Banyumas, especially in upper service materials. The main premise of this study is that volleyball learning packaged through play can create a more active, contextual, fun, and meaningful learning experience than learning that is centered solely on the repetition of techniques. The research hypothesis states that there is an increase in student learning outcomes after the application of the Game-Based Learning model in the affective, cognitive, and psychomotor domains. This study uses a quantitative approach with a one-group pretest-posttest design experiment. The study participants totaled 38 students, consisting of 13 male students and 25 female students. The research instruments include knowledge tests, attitude assessment sheets, upper service skills rubrics, and learning observation sheets. Data were analyzed using descriptive statistics, Shapiro-Wilk normality test, paired sample t-test, Wilcoxon test, and Cohen’s effect measure d. The results of the study showed an increase in the average score in all areas of learning outcomes. The affective score increased from 51.26 to 57.92; cognitive score increased from 83.16 to 91.05; and psychomotor scores increased from 62.13 to 69.08. The difference test showed a significant increase in the affective, cognitive, and psychomotor domains with a p value of < 0.05. The effect size showed a large influence on the affective domain and a moderate influence on the cognitive and psychomotor domains. Thus, the research hypothesis is accepted. The Game-Based Learning model has proven to be effective in improving students’ overall volleyball learning outcomes. Keywords: Game-Based Learning; learning outcomes; ball; top serve; physical education.